A Double Multiple Stream Tube (DMST) routine for site assessment to select efficient turbine aspect ratios and solidities in real marine environments - Pucci Micol (EDP Sciences, 2021)
A MATLAB routine, based on a Double Multiple Stream Tube model, developed to quickly predict the performance of cross-flow hydrokinetic turbine, here is presented. The routine evaluate flow data obtained with the open-source marine circulation code SHYFEM. The tool can establish the best locations to place tidal devices taking into account bathymetric constraints and the hydrokinetic potential. Hence, it can be used to decide the best set of geometrical parameters. The geometrical variables of our analysis are turbine frontal area, aspect ratio and solidity. Several sub-models, validated with 3D and 2D CFD simulations, reproduce phenomena such as dynamic stall, fluid dynamic tips losses and the lateral deviation of streamlines approaching the turbine. As a case study, the tool is applied to an area of the northern Adriatic Sea. After having identified some suitable sites to exploit the energy resource, we have compared behaviours of different turbines. The set of geometrical parameters that gives the best performance in terms of power coefficient can vary considering several locations. Conversely, the power production is always greater for turbine with low aspect ratio (for a fixed solidity and area). Indeed, shorter devices benefit from higher hydrokinetic potentials at the top of the water column.